When Algorithms Govern Solidarity: A Fiqh Muamalah Perspective on Ethical Takaful in The Age of Artificial Intelligence - Kharisma, Dita; Nofrianto, Nofrianto; Rahmawati, Yuke; Salic, Jawad Z. (Suhuf: International Journal of Islamic Studies, 2026)
Background: The growing use of artificial intelligence (AI) in Islamic financial services raises a critical ethical question: can takaful remain faithful to its foundations of taawun (mutual solidarity) when risk-sharing decisions are increasingly made by algorithms rather than morally accountable individuals? Objective: This study examines whether AI integration in underwriting, risk scoring, and claims management challenges the ethical coherence of takaful from the perspective of fiqh muamalah and maqasid Sharia. Methodology: Using a normative-conceptual approach, the research draws upon Islamic legal principles and contemporary AI ethics to analyze how algorithmic governance reshapes accountability within takaful institutions. Results: The analysis reveals that AI redistributes decision authority in ways that create opacity, bias, and accountability gaps, and risks shifting ethical responsibility away from human agents who bear taklif. Conclusion: Takaful can remain ethically sound only if accountable human moral agency remains central to its governance structure. The study proposes an Ethical Thresholds Framework to guide AI adoption, emphasizing transparency, human oversight, and strengthened Sharia governance in digital takaful systems. Implication: Regulators, Sharia supervisory boards, and takaful operators should require explainable, fair, auditable, and human-supervised AI systems to preserve accountability, taawun, and the ethical legitimacy of digital takaful.